Improved Pharmacokinetics of Sumatriptan With Breath Powered™ Nasal Delivery of Sumatriptan Powder. Issue 8 (28th August 2013) - Obaidi, Mohammad; Offman, Elliot; Messina, John; Carothers, Jennifer; Djupesland, Per G.; Mahmoud, Ramy A.
Abstract : Objectives.—: The purpose of this study was to directly compare the pharmacokinetic (PK) profile of 22‐mg sumatriptan powder delivered intranasally with a novel Breath Powered™ device (11 mg in each nostril) vs a 20‐mg sumatriptan liquid nasal spray, a 100‐mg oral tablet, and a 6‐mg subcutaneous injection. Background.—: A prior PK study found that low doses of sumatriptan powder delivered intranasally with a Breath Powered device were efficiently and rapidly absorbed. An early phase clinical trial with the same device and doses found excellent tolerability with high response rates and rapid onset of pain relief, approaching the benefits of injection despite significantly lower predicted drug levels. Methods.—: An open‐label, cross‐over, comparative bioavailability study was conducted in 20 healthy subjects at a single center in the USA. Following randomization, fasted subjects received a single dose of each of the 4 treatments separated by a 7‐day washout. Blood samples were taken pre‐dose and serially over 14 hours post‐dose for PK analysis. Results.—: Quantitative measurement of residuals in used Breath Powered devices demonstrated that the devices delivered 8 ± 0.9 mg (mean ± standard deviation) of sumatriptan powder in each nostril (total dose 16 mg). Although the extent of systemic exposure over 14 hours was similar following Breath Powered delivery of 16‐mg sumatriptan powder and 20‐mg liquid nasal spray (area under the curve [AUC]0‐∞ 64.9 ng*hour/mL vs 61.1 ng*hour/mL), sumatriptan powder, despite a 20% lower dose, produced 27% higher peak exposure (Cmax 20.8 ng/mL vs 16.4 ng/mL) and 61% higher exposure in the first 30 minutes compared with the nasal spray (AUC0‐30 minutes 5.8 ng*hour/mL vs 3.6 ng*hour/mL). The magnitude of difference is larger on a per‐milligram basis. The absorption profile following standard nasal spray demonstrated bimodal peaks, consistent with lower early followed by higher later absorptions. In contrast, the profile following Breath Powered delivery showed higher early and lower late absorptions. Relative to the 100‐mg oral tablet (Cmax 70.2 ng/mL, AUC0‐∞, 308.8 ng*hour/mL) and 6‐mg injection (Cmax 111.6 ng/mL, AUC0‐∞ 128.2 ng*hour/mL), the peak and overall exposure following Breath Powered intranasal delivery of sumatriptan powder was substantially lower. Conclusions.—: Breath Powered intranasal delivery of sumatriptan powder is a more efficient form of drug delivery, producing a higher peak and earlier exposure with a lower delivered dose than nasal spray and faster absorption than either nasal spray or oral administration. It also produces a significantly lower peak and total systemic exposure than oral tablet or subcutaneous injection.